ANALISIS DAN PERANCANGAN SISTEM KOMPENSASI KARYAWAN KAFE BERBASIS JOB VALUE (STUDI KASUS PADA KAFE XY) - Verdi Firmansyah; Rahadiyanto Tri Wibowo; Ziju Wildan Fadilah; Ariq Athallah; Yusuf Yusuf; Lindawati Kartika (Jurnal Pijar, 2023)
This study aims to assist and provide input to XY cafe owners in salary mapping using the adhered and overlapping methods and using the Hay method in determining compensation factors. The data collection method was carried out through descriptive quantitative research, in which respondents were interviewed to obtain employee profile and salary data to analyze the structure of employee salary mapping. The results of the analysis show that the actual total starting salary for XY cafe is IDR 28,900,000 while the total salary using the adhered method is IDR 30,261,175, this indicates an increase in employee salaries with a difference of IDR 1,361,175. Whereas with the overlapping method the total salary is IDR 30,626,000, this shows an increase in employee salaries with a difference of IDR 1,726,000.